French Sustainable Fashion Diplomacy: Soft Power Strategies in Public Diplomacy - Raina Alliyah Destymiradz; Windy Dermawan (Universitas Muhammadiyah Sorong, 2026)
This article examines how France utilizes sustainable fashion as a soft power-oriented public diplomacy strategy. Using a qualitative descriptive case study approach, the research draws on secondary data from policy documents, industry reports, global perception indicators, academic literature, and international media coverage. The study argues that France’s sustainable fashion diplomacy should not be understood as direct evidence of increased French influence, but rather as a qualified soft power resource through which France connects cultural prestige, regulatory credibility, and environmental responsibility. Through the Anti-Waste for a Circular Economy Law, The Fashion Pact, and anti-fast fashion measures, France transforms fashion governance into an internationally visible ecological narrative circulated through media, fashion institutions, transnational networks, and non-state actors. However, this strategy remains vulnerable to credibility challenges, particularly greenwashing and the possible perception of eco-protectionism. The article contributes to International Relations scholarship by showing how a traditional cultural industry can be repositioned as a site where culture, sustainability, public diplomacy, national reputation, and soft power intersect.